2009
DOI: 10.3748/wjg.15.3799
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of PTCH1a gene in a subset of gastric cancers

Abstract: RESULTS: Methylation of PTCH1a TRR was observedin AGS cells and a subset of gastric cancer tissues (32%, 55/170), while no methylation amplification products were observed in any normal tissues by MSP. The methylation of PTCH1a TRR was correlated negatively with PTCH1 expression (Spearman's r = -0.380, P = 0.000). However, methylation of PTCH1a TRR was not related to the gastric cancer patients' clinical features, such as sex, age of onset, clinical stage, lymph node metastasis or histological grade. The methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…The presence of large rearrangements and/or deletions cannot be excluded as they cannot be detected by direct sequencing, although the detected 32 heterozygous changes provide some evidence against frequent and large PTCH1 deletions in the studied cancers. Alternative mechanisms for PTCH1 downregulation could include, e.g., epigenetic silencing of PTCH1 or constantly activated MAPK signaling [31,32]. We have recently observed that serrated adenocarcinomas are characterized by BRAF and KRAS mutations [30], and also in this study, 78% of the analyzed tumors carried a mutation in either gene (Table 3).…”
Section: Mutationmentioning
confidence: 74%
“…The presence of large rearrangements and/or deletions cannot be excluded as they cannot be detected by direct sequencing, although the detected 32 heterozygous changes provide some evidence against frequent and large PTCH1 deletions in the studied cancers. Alternative mechanisms for PTCH1 downregulation could include, e.g., epigenetic silencing of PTCH1 or constantly activated MAPK signaling [31,32]. We have recently observed that serrated adenocarcinomas are characterized by BRAF and KRAS mutations [30], and also in this study, 78% of the analyzed tumors carried a mutation in either gene (Table 3).…”
Section: Mutationmentioning
confidence: 74%
“…Lack of methylation at the alternative exon 1B was reported for human medulloblastoma [ 31 , 32 ] whereas others showed methylation in exon 1A [ 33 ]. Methylation of exon 1A was also found in gastric cancer samples [ 34 ] and exon 1B was methylated in fibroma and dermoids [ 35 ], in basal cell carcinoma [ 36 ] but not in squamous cell cervical cancer or ovarian cancer [ 37 ]. Moreover it was reported that the Ptch promoter in medulloblastoma from Ptch heterozygous mice is not methylated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 5-aza-dc, a well-established promoter methylation inhibitor [31, 50], was employed. As shown, 5-aza-dc (1 µM) significantly inhibited HHIP promoter methylation in AGS cells (Fig.…”
Section: Resultsmentioning
confidence: 99%